High-Intensity Functional Training Improves Cardiorespiratory Fitness and Neuromuscular Performance Without Inflammation or Muscle Damage. Issue 3 (27th March 2022) - Posnakidis, Georgios; Aphamis, George; Giannaki, Christoforos D.; Mougios, Vassilis; Aristotelous, Panagiotis; Samoutis, George; Bogdanis, Gregory C.
Abstract: Posnakidis, G, Aphamis, G, Giannaki, CD, Mougios, V, Aristotelous, P, Samoutis, G, and Bogdanis, GC. High-intensity functional training improves cardiorespiratory fitness and neuromuscular performance without inflammation or muscle damage. J Strength Cond Res 36(3): 615–623, 2022—We examined the effects of high-intensity functional training (HIFT) on cardiorespiratory and neuromuscular performance, as well as on inflammatory and muscle damage markers. Thirteen physically active healthy volunteers (aged 28.3 ± 3.8 years, 5 men and 8 women) underwent 8 weeks of a group HIFT program performed 3 times per week. Each session consisted of 4 rounds of a 9-exercise circuit (30-second exercise and 15-second recovery). During the first and last weeks of training, venous blood was sampled daily to monitor changes in serum C-reactive protein (CRP) and creatine kinase (CK). After 8 weeks of HIFT, body fat decreased by 0.64 ± 1.01 kg ( p = 0.041), maximal oxygen uptake improved by 1.9 ± 2.2 ml·kg −1 ·min −1 ( p = 0.009), countermovement jump by 2.6 ± 1.5 cm ( p = 0.001), bench press 1-repetition maximum (1RM) by 4.5 ± 3.8 kg ( p = 0.001), maximum number of bench press repetitions at 65% 1RM by 4 ± 5 repetitions ( p = 0.03), and abdominal muscle endurance by 6 ± 4 repetitions ( p < 0.001). In both week 1 and week 8 of training, CK increased mildly in the morning after the first session of the week (main effect for day, p = 0.008), whereas no significant changes were observed in CRP ( p = 0.31). During week 8, CK on all days was ∼32% lower compared with week 1 (160 vs. 235 U·L −1 ; main effect of week 1 vs. week 8, p = 0.027), whereas CRP remained unchanged ( p = 0.225). This HIFT program was effective in improving cardiorespiratory and neuromuscular physical fitness without causing significant inflammation or muscle damage in physically active subjects.